(untitled) (Journal of Laboratory Animal Science, 2024)
Animals have been models for humans since the dawn of medicine as per the first medical handbook ‘Corpus Hippocraticum’ (around 400 B.C). In an era where no anaesthetic agents were identified, live animals such as dogs, pigs and monkeys were the subjects for vivisections to study human anatomy. Reverend Stephen Hales (1677–1761) inserted a brass pipe into a major blood vessel in the neck of a live horse through which a glass tube was sent and introduced the concept of blood pressure to the scientific fraternity (van Zutphen, 2001; Lewis, 1994; Felts, 1977). Similar to these, different animals have been the models for development of many fields of medicine especially for the benefit of humans. The objective of this article is to describe the role played by the Faculty of Medicine, University of Colombo (UCFM) as the forerunner in laboratory animal science in Sri Lanka to facilitate laboratory animal use in medical education, research, ethics and laboratory animal science education.